The Impact of Recent Developments in the European Economic Community on National Labour Law Systems - Blanpain, R. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1976)
The author evaluates after some twenty years of experience, the impact of the European Economic Community on national labour laws.